2021
DOI: 10.1186/s12889-021-10712-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of respiratory dust exposure and lung functions among workers in textile mill (Thamine), Myanmar: a cross-sectional study

Abstract: Background Airborne dusts are being potentially harmful for workers in occupational environment. Exposure to respirable dust is the most important concern in textile workers for the widespread of occupational lung diseases, especially more serious in developing countries. The aim of the study was to assess the respirable dust exposure and associated factors of lung functions among textile workers. Methods A cross-sectional study was carried out at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
(29 reference statements)
2
10
1
1
Order By: Relevance
“…We found similar results in other studies [ 25 , 26 , 27 ]. However, the current results showed no significant relationship between the duration of exposure and the decline in lung function, which is inconsistent with previous studies [ 2 , 28 ]. A possible reason for this difference is that similar exposure times do not necessarily imply similar total doses of exposure.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found similar results in other studies [ 25 , 26 , 27 ]. However, the current results showed no significant relationship between the duration of exposure and the decline in lung function, which is inconsistent with previous studies [ 2 , 28 ]. A possible reason for this difference is that similar exposure times do not necessarily imply similar total doses of exposure.…”
Section: Discussioncontrasting
confidence: 99%
“…The initial effects of dust on the lungs are characterized by reversible respiratory symptoms and worsened lung function [ 1 ]. Occupational dust exposure can induce pulmonary inflammatory cascades and structural damage, leading to decreased lung function and other dust-related lung diseases, including sinus disease, respiratory irritation, and chronic obstructive pulmonary disease (COPD), which is globally recognized as a serious public health problem [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of dust has the potential to cause lung function and respiratory disorders, which are influenced by the type of particles, duration of exposure, particle content, and particle size (Soeript, 2008). Similar observations were reported in Oo'sresearch in 2017 in Thamie, Myanmar where the exposure to inhaled dust has a risk value of 4.12 times experiencing respiratory problems (Oo et al, 2021).…”
Section: The Relationship Of Respirabledust Exposure With Respiratory...supporting
confidence: 84%
“…This study is consistent with Oo (2021) study in Thamie, Myanmar, where 105 workers (50.7%) frequently reported inhaling textile dust with a concentration greater than 3 mg/m 3 , with an average respirable dust concentration of 3.3 mg/m 3 and a range between 2.4 mg/m 3 and 4.1 mg/m 3 . P value 0.001 indicated significant results between occupational respiratory disease and exposure to respirable dust (Oo et al, 2021).…”
Section: The Relationship Of Respirabledust Exposure With Respiratory...mentioning
confidence: 98%
“…Other studies reported exposure dependent relationship between cotton dust, lung function and reported that increased exposure of cotton dust was significantly associated with a reduction in FVC (OR=2) and FEV1 (OR=1.83). 25 Another important finding of this study is the association of decreased lung function (i.e., FVC, FEV1 for non-smokers, and FEV1/FVC ratio for smokers) with the duration of work. Long-term cotton dust exposure is associated with obstructive lung diseases 6 , while more experienced workers are at a greater risk for developing decrements in lung function 6,24 .…”
Section: Discussionmentioning
confidence: 61%